Dapur dan Allah: Rekonstruksi Teologis Makna Sosio-Religi-Kultural Dapur dalam Masyarakat Minahasa - Denni Pinontoan (Asosiasi Teolog Indonesia, 2022)
This article focuses discussion on the kitchen as a space and place in the socio-religio-cultural practice of the Minahasan people. One customary trait of the Minahasan people is their penchant for parties, wherein having a meal together plays an important part. All that is served on the dining table starts from the kitchen. Therefore, the kitchen is a place and space that is integrated with the social order. This article intends to demonstrate how the kitchen serves not only as a place for culinary activities, but it also functions as a space whereby God’s presence is reflected in personal, family, and communal life. Out of the theological reconstruction of its meaning, we see how the kitchen is an important part of efforts to maintain kinship, community relations, as well as hospitality, all as praxis that stems from experiencing God’s presence.